KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN 001 CENTER MAMBI KABUPATEN MAMASA - Ilham Anas; Wahira; Muh. Ardiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to investigate how the principal's instructional leadership at SDN 001 Center Mambi, Mamasa Regency, serves as a catalyst for the Merdeka Curriculum's implementation. This study's backdrop is the important role that school principals play in spearheading learning change, particularly in the context of the Merdeka Curriculum framework, which prioritizes teacher collaboration, student-centered learning, and learning freedom. In order to gain a comprehensive knowledge of the principal's instructional leadership techniques, this study employs a qualitative methodology with a case study design. Purposively, the research site was chosen, and the principal, instructors, and students participated in in-depth interviews, participant observation, and documentation studies to gather data. The interactive model of Miles, Huberman, and Saldana—which incorporates data condensation, data display, and conclusion drawing—was employed in the data analysis technique. Triangulation of source, technique, and time was used to guarantee the validity of the data. The findings demonstrated that the principal exhibited effective instructional leadership by organizing school activities, monitoring student progress, encouraging teacher cooperation, and cultivating a positive learning environment. In addition, the principal set an example by adjusting to curricular modifications and encouraging educators to use creativity in the classroom. The successful implementation of the Merdeka Curriculum at the school level was largely due to this leadership.